Analisis Frekuensi Kata dalam Cerpen: Studi Linguistik Korpus dalam Karya Sastra - Ariyanti, Maytha Carissa (TALENTA, 2025)
This study aims to analyze the frequency of words in the translated short story The Tale of Johnny Town-Mouse by Beatrix Potter translated by Arya Bisma into The Tale of Johnny Town-Mouse. A qualitative approach is used to identify patterns of word usage as a reflection of the themes, characters, and narrative elements of the story. Then the data analysis technique was carried out using the web-based software Voyant Tools, which systematically counts the number of occurrences of each word in the text. The results showed that words with the highest frequency such as Timmy, Willie, and Johnny reflected the story's focus on the interactions between the main characters. The word keranjang indicates the importance of physical elements associated with rural life, while town and mouse emphasize the setting and theme of city life. In addition, descriptive words such as suara and kembali reinforce the atmosphere and plot of the story. This study shows that corpus analysis can reveal linguistic patterns that reflect important themes and elements in literary works. This approach not only helps to understand language structure and style, but also provides insight into the social and cultural context that influenced the story. Thus, this study emphasizes the relevance of the corpus linguistics approach in literary analysis